Aerodynamic pitch control design for reversal of missile's flight direction. (July 2014) - Kim, Yoonsoo; Kim, Byoung Soo; Park, JeongHo
This paper proposes a purely aerodynamic pitch control design scheme for agile missiles that need to reverse their flight directions for tracking a target. The main challenge in performing this kind of manoeuvre is that the missiles may enter the high angle of attack domain in which aerodynamic actuation is ineffective. Assuming that reliable aerodynamic data are available for the flight envelope, a systematic search algorithm is employed to find an aerodynamic control parameter and the motor thrust activation time, so as to enable the missile's required manoeuvre. The strength of the proposed design scheme is that no third control mechanism such as thrust vectoring is required for the missile control even in the high angle of attack domain. The proposed design scheme is tested on aerodynamic data available in literature, and is shown to be promising via simulations.